2019
DOI: 10.1253/circj.cj-19-0323
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tobacco Smoking on Cardiovascular Disease

Abstract: smoking and the risk of venous thromboembolism (VTE) is an as-yet-unsolved clinical question. 10,11 Because VTE events occur after censoring the data to evaluate deaths caused by cancer or CVD, data regarding VTE events have not been counted and thus excluded from analysis. However, when VTE events are analyzed as the only outcome, heavy smoking is associated with provoked VTE. 12 Prevalence of Tobacco SmokingThe estimated global prevalence of tobacco smoking in 2010 was 36.6% for men and 7.5% for women. 13 In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
134
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(187 citation statements)
references
References 69 publications
6
134
0
13
Order By: Relevance
“…The level of the HDL fraction inchildren exposed to SHS from both parents was considerable decreased. This finding is similar with other study reffering to otherwise healthy children [5], with HDL low levels secondary to SHS, witch increase considerably the future cardiovascular risk for these children [6,8,9]. A large study including 11,550 children from USA, aged between 12 and 19 years , witch explored the association between SHS and lipoprotein cholesterols (total cholesterol, HDL-cholesterol, non-HDL-cholesterol, LDL-cholesterol, and triglycerides), showed that SHS exposure associated higher total cholesterol, higher LDL-cholesterol and lower HDL-cholesterol [13], correlation which, in our study, was significant only regarding HDL-C (p=0.034).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The level of the HDL fraction inchildren exposed to SHS from both parents was considerable decreased. This finding is similar with other study reffering to otherwise healthy children [5], with HDL low levels secondary to SHS, witch increase considerably the future cardiovascular risk for these children [6,8,9]. A large study including 11,550 children from USA, aged between 12 and 19 years , witch explored the association between SHS and lipoprotein cholesterols (total cholesterol, HDL-cholesterol, non-HDL-cholesterol, LDL-cholesterol, and triglycerides), showed that SHS exposure associated higher total cholesterol, higher LDL-cholesterol and lower HDL-cholesterol [13], correlation which, in our study, was significant only regarding HDL-C (p=0.034).…”
Section: Resultssupporting
confidence: 92%
“…While the pulmonary consequences of SHS exposure are clinically apparent in childhood, the cardiovascular effects of SHS exposure are occult but substantial [2] It appears that SHS exposure in early childhood, even in utero, can cause persistent lipoprotein changes later in life [3], increased incidence of obesity [4], lower high-density lipoprotein cholesterol (HDL C) levels in children [5]. Chemicals from tobacco second-hand smoke have several bad effects on various cardiovascular diseases, including coronary artery disease, ischemic stroke, non-traumatic subarachnoid haemorrhage [8], platelet activation, stimulation of the coagulation cascade [9]. Kalishadi and colleagues [10 showed that both smoking and exposure to smoke are associated with an increased risk of cardiometabolic risk factors and metabolic syndrome in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, prolonged alcohol use is linked to impaired mucociliary clearance and lung function, and methamphetamine use is linked to noncardiac pulmonary edema, ARDS, alveolar hemorrhage, pneumonia, and pneumoconiosis (10,11). In addition, cocaine, methamphetamines, alcohol, tobacco, and opioids are reported to have adverse effects on the cardiovascular system, including hypertension, ischemia, venous thromboembolism, and brain hemorrhage (5,12,14). Substance use disorders can also increase the risk of adverse COVID-19 outcomes through immunosuppression (3).…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence that opioids, alcohol, methamphetamines, smoking, and vaping all have strong immunosuppressive effects, resulting in greater susceptibility to infection, more severe and longer lasting illnesses, and lower levels of protective antibodies in the blood (3,4). In addition, some substance use disorders, such as tobacco (smoking), cocaine, and alcohol use disorders, are associated with adverse cardiovascular effects, including hypertension, ischemia, venous thromboembolism, and brain hemorrhage (5,6).…”
mentioning
confidence: 99%
“…Cigarette smoking is a major public health problem in many countries throughout world. The harmful effects of smoking on human health are well documented in both in vivo and in vitro studies; smoking is known to be a major risk factor for respiratory diseases, cardiovascular disorders, hormonal imbalance, cancer, and disturbances of the reproductive system [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. A decrease in semen parameters, with a higher percentage of sperm with abnormal morphology, is observed in smoking men.…”
Section: Introductionmentioning
confidence: 99%